Where to for collaboration in land and water policy development in Aotearoa New Zealand? Guidance for authorising agencies. (3rd April 2022) - Kirk, Nicholas; Robson-Williams, Melissa; Bammer, Gabriele; Foote, Jeff; Butcher, Lian; Deans, Neil; Harmsworth, Garth; Hepi, Maria; Lilburne, Linda; Nicholas, Barbara; Small, Bruce; Turner, James A.; et al.
ABSTRACT: For the past decade, collaboration has been the preferred method of devising land and water policy in Aotearoa New Zealand to achieve agreed outcomes. However, the use of collaboration in policymaking is at a crossroads, as some argue it is unrealistic to expect stakeholders and tangata whenua with competing interests to work in partnership on contentious policy issues. To help clarify the future direction of collaboration, this paper provides authorising agencies (those with responsibility for the policy problems) with prompts to reflect ex ante on the advantages and disadvantages of pursuing collaboration. Based on a retrospective review of collaborations in New Zealand's land and water policymaking, and a two-day symposium with collaboration practitioners, we identify situations that are potentially less suited to collaboration owing to factors that are challenging to overcome through process design. Four issues that affect the success of collaborations are identified: the nature of the policy problem, the personal and collective qualities of those involved, power relationships, and the collaborative process. Finally, we draw together practical lessons from history, the symposium, and the literature to develop a list of questions for authorising agencies to use to reflect on the advantages and disadvantages of pursuing collaboration.